Characterization of mammary gland signal intensity by magnetic resonance imaging - Xavier Leonardo Jaramillo-Chaustre; Alici Ester Serantes-Gómez; Jhon Jairo Bustamante-Cano (Iteckne, 2016)
Magnetic resonance imaging (MRI) has been introduced gradually to the Veterinary Diagnostic. In this research MRI was used for the study of mammary gland in  healthy  dogs,  in  T1  enhanced series  of  mammary  gland  and  surrounding  structures  in  twelve  bitches. With the obtained images, tables of signal intensity (SI) by manual planimetry to observe the variation in grayscale in a same structure and take it as reference subsequently developed, addition to become acquainted with the software used. To validate the technique used in the images they were  considered  three structures  (air,  fat and muscle) which IS showed significant difference between  glandular  breast  tissue  (IS  184.8  ±  28.2)  and  regional lymph nodes (IS 51.3 ± 5,4), allowing to determine the benchmark for the study. It is concluded that the use of a low field equipment of MRI provides sufficient information for the mammary gland, ducts and regional lymph nodes  study  in  dogs,  making  a  complete  anatomical evaluation and identification of such structures.